2022
DOI: 10.1080/17843286.2021.2024384
|View full text |Cite
|
Sign up to set email alerts
|

Should I, can I, dare I? Patients’ view on stopping long-term antidepressant use, a qualitative study

Abstract: Background and aim:The rise in long-term antidepressant use is concerning. Long-term antidepressant (AD) use, much longer than recommended by guidelines, can result in risk of adverse events and generate unnecessary costs. In order to mitigate these risks, patients views about their antidepressants and how to discontinue need to be taken into account. We aimed to explore patients' experiences and views of discontinuing long-term AD, barriers and facilitators of discontinuation and required support. Methods: Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
3
7
0
Order By: Relevance
“…This was evident in a recent large online survey ( n > 1000) which revealed that less than 5% of patients reported being told anything about antidepressant withdrawal effects by their prescribers 39 . Our findings are also supported by another recent qualitative study, where participants highlighted the need for more support from healthcare professionals, a greater focus on non‐pharmacological approaches in primary care to address unnecessary antidepressant use, and increased awareness of the withdrawal process 40 . Importantly, these concerns are further reflected in national guidelines where in a 2019 report Public Health England recognised the significant challenges individuals face when withdrawing from antidepressants and called for the implementation of specialised support services and a helpline for individuals attempting to withdraw from antidepressants, 41 a need highlighted by patients as being currently lacking 42,43 .…”
Section: Discussionsupporting
confidence: 76%
“…This was evident in a recent large online survey ( n > 1000) which revealed that less than 5% of patients reported being told anything about antidepressant withdrawal effects by their prescribers 39 . Our findings are also supported by another recent qualitative study, where participants highlighted the need for more support from healthcare professionals, a greater focus on non‐pharmacological approaches in primary care to address unnecessary antidepressant use, and increased awareness of the withdrawal process 40 . Importantly, these concerns are further reflected in national guidelines where in a 2019 report Public Health England recognised the significant challenges individuals face when withdrawing from antidepressants and called for the implementation of specialised support services and a helpline for individuals attempting to withdraw from antidepressants, 41 a need highlighted by patients as being currently lacking 42,43 .…”
Section: Discussionsupporting
confidence: 76%
“…advice is generally in line with previous PATD/rPATD literature, regardless of patient population and health care setting. 16 Nevertheless, the findings discussed above (i.e., the potential influence of specific concerns and past experiences on patients' deprescribing willingness) as well as the qualitative literature on patient barriers to psychotropic deprescribing 8,12,13 suggest that most older psychiatric outpatients do have significant barriers to engage in deprescribing in an actual clinical situation, in particular of their psychotropic treatment. Although some studies have adjusted the PATD/rPATD questionnaire to focus on specific drug classes (e.g., alpha-blockers, 28 proton pump inhibitors), 29 the original questionnaire is not medication-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Psychotropic deprescribing can, however, be a complex process 7 . Psychotropics are often used long‐term and patients may be reluctant to stop these medications, 8 while underlying psychiatric morbidity, pharmacological dependence and withdrawal symptoms may further complicate the deprescribing process. In addition, health care professionals report multiple barriers to psychotropic deprescribing, for example, lack of qualifications and resources 9,10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority (86%) of antidepressants are prescribed in primary care [20], placing general practitioners (GPs) in a unique position to also deprescribe (the planned and supervised process of dose reduction or cessation [21]). However, antidepressant deprescribing can be complex and does not routinely occur in clinical practice [22,23] with reported barriers by both GPs and patients, including fear of relapse or recurrence and a lack of quality guidelines for deprescribing [24][25][26][27]. Discontinuation symptoms such as tremors, sweating, anxiety, mood swings, and electric shock sensations are also associated with stopping antidepressants [28][29][30] and can be confused with relapse or recurrence.…”
Section: Introductionmentioning
confidence: 99%